Changes in structural, morphological, and corrosion properties of CrN thin film effected by varying N2 pressure In the sputtering process - Wongtanasarasin, Wichuda; Sakdanuphab, Rachsak; Suwansukho, Kajpanya; Sakulkalavek, Aparporn (My University, 2015)
In this study, we investigate a facet of the fabrication process of chromium nitride (CrN) film intended as a protective coating for pineapple blades. CrN thin films were deposited on unpolished stainless steel substrates (AISI304) by DC reactive magnetron sputtering in Ar+N2 gases. In principle, the proportion of nitrogen partial pressure to the total pressure in the sputtering process should have considerable effects on the CrN film's chemical composition, its crystal structure, its hardness, and its corrosion resistance. We tested this supposition out by using several different nitrogen partial pressures in the sputtering process and observed the films deposited. The coatings were deposited at five different nitrogen partial pressures of 4.0×10-4 mbar, 8.0×10-4 mbar, 1.2×10-3 mbar, 1.6×10-3 mbar, and 2.0×10-3. The deposition times were controlled to achieve 5-μm thick films in each deposition. The films were analyzed by several analytical methods, such as X-ray diffraction (XRD), scanning electron microscope, micro-hardness and potentiostat in pineapple juice. The XRD spectra of the films showed face-centered cubic structure with (200) preferred orientation, positively identifying them as Cr2N and CrN thin films. The calculated d-spacing and lattice parameter of the CrN films increased with increasing nitrogen partial pressure; the ranges were 0.283-0.287 nm and 0.491-0.497 nm, respectively. The cross-section morphology of the CrN films reveals the columnar grain growth with a high density. The crystal structure and the grain texture correspond with the hardness property. The films corrosion potential, an indicator of their corrosion property, was varied from -0.14 to -0.05 volts with varying nitrogen pressure. The most corrosion resistant and the good hardness were the film fabricated at the nitrogen partial pressure of 1.2×10-3 mbar.
Keywords: Corrosion; CrN thin film; DC reactive magnetron sputtering